Usia Pernikahan dan Kontrasepsi Terhadap Tingkat Fertilitas Wanita - Syaif Adiansyah; Raden Muhamad Azzam; Mohamad Gea Subagja (PT. Hasba Edukasi Mandiri, 2025)
This study examines the factors influencing fertility rates (birth rates) in Banten Province, focusing specifically on the analysis of age at first marriage, age at first pregnancy, and contraceptive use. Data were obtained through literature review and secondary data analysis from the 2024 National Socio-Economic Survey (Susenas). The findings indicate that women who marry and become pregnant before the age of 20 tend to have higher fertility rates, especially in rural areas such as Lebak and Pandeglang Regencies. On the other hand, the use of contraceptive methods—particularly injections and pills—has proven effective in reducing birth rates, with an increasing trend of usage. Education and access to reproductive health information also play a significant role in managing fertility levels. The study recommends enhancing reproductive health awareness and improving access to contraceptives, particularly in regions with high fertility rates.